Formación pedagógica y aprendizajes vitales de maestros becarios en la Universidad Industrial de Santander, Colombia (2021)
The experience of teacher education in the context of the Master’s degree in Pedagogy at a Colombian university and with the sponsorship of the national government is the main theme of this documentary exercise, carried out from the teaching experience guided by university teachers who managed to transcend theoretical learning to make it vital. The experience of the participating teachers indicates that there was a direct connection with the groups of teachers. The exercise was carried out from a qualitative action-research, as well as from a particular case study in which thorough analyses are made from the participant observation of the researchers from their own pedagogical experience. It is found that, as a scenario and common point of the pedagogical experience with the scholarship holders, knowledge could be strengthened, but at the same time touching the sensitivity and emotionality of those who, from the diverse contexts of performance, questioned their pedagogical practices and sought new horizons of meaning, becoming their own researchers. The motivation and the prevailing desire to transform the school from the investigation of their own pedagogical practices, having as a transversal theme the enormous work for emotional education, life stories, and critical thinking, constitute the added values that teachers care forand now zealously take to the classrooms, as depositories of renewed pedagogical knowledge that particularly integrates theoretical learning with the lifeworld of their students.